Morphology, roughness, and surface loss of sound enamel submitted to different acid etching agents and different durations of application - Landmayer , Karin; Pastori, Isadora Catelan; Ordóñez-Aguilera, Juan Fernando; Iatarola, Bruna de Oliveira; Zezell, Denise Maria; Francisconi-dos-Rios, Luciana Fávaro (Brazilian Dental Science, 2026)
Objective: Knowledge about the effects of different phosphoric acids can help clinicians choose the appropriate acid etchant, preserving dental structure without compromising bond strength. This study aimed to analyze the morphology, surface loss, and roughness of different acid etching agents, especially a self-limiting phosphoric acid, at different time intervals. Material and Methods: Bovine enamel specimens were allocated into experimental groups (n = 5). The surfaces were treated with acid etchant (UE: UltraEtch; C37: Condac37; PE37: Power Etching 37%; DGC: Dental Gel Conditioner; SE: Scotchbond Etchant) for 15, 30, 60, 90, and 120 s. Surface loss and roughness were evaluated with an optical profilometer, and morphological analyses was performed by Scanning Electron Microscopy. Data were statistically analyzed (α=0.05). Results: The surface loss increased for all acids over time, except for UE. Up to 60 s, none of the acids promoted different surface loss. For 90 s, UE showed the smallest loss, and SE exhibited the greatest loss; for 120 s, UE had the smallest loss, while DGC and SE had the highest. The roughness increased for all acids over time, including UE, except for 90 s. For 90 s, DGC promoted the highest surface roughness, while UE, PE37, and SE showed the smallest. Compared to the control, all acids showed significant differences in structural loss and roughness. Finally, the type 2 etching pattern predominated. Conclusion: UltraEtch exhibited a self-limiting etching behavior, even though it causes an increase in surface roughness, it does not promote a significantly increasing surface loss over time. KEYWORDS Acid Etching; Enamel; Morphology; Phosphoric Acid; Surface Properties.